Variable rate air‐assisted spray based on real‐time disease spot identification. Issue 1 (17th October 2022) - Zhang, Jinhui; Yin, Hao; Zhou, Liangfu; Gu, Chao; Qiu, Wei; Lv, Xiaolan; Sun, Hao; Yu, Hongfeng; Zhang, Zhengwei
Abstract: Background: Currently, the variable‐rate application (VA) of agrochemicals on fruit trees is based on canopy volume and biomass. The canopy volume has a significant relationship with disease resistance and degree of disease incidence. Therefore, this study proposes a VA method that uses deep convolutional neural networks for real‐time recognition of disease spots on pear trees. Furthermore, it specifies the limitations and application scenarios of the disease spot recognition. Field performance tests were conducted to verify the performance of the proposed VA system. Results: The results showed a mean average precision, precision, and recall of 87.42%, 83.76%, and 87.23%, respectively. The spot recognition rate was 81.3% when the canopy sampling distance, spot diameter, and canopy porosity were 1.2 m, 4–8 mm, and 55.76%, respectively. The results indicate that the proposed VA system saved 51.9% spray volume compared to conventional methods while ensuring quality. Conclusion: Compared to the traditional constant rate model, the proposed VA technology based on real‐time disease spot identification can reduce spraying in nondiseased areas, thereby abandoning the previous saturation application practice and significantly reducing pesticide use. © 2022 Society of Chemical Industry. Abstract : This study proposes a variable rate application method that uses deep convolutional neural networks for real‐time recognition of disease spots on pear trees. Furthermore, it specifies the limitations and application scenarios of the disease spot recognition.